2017
DOI: 10.1177/0886260517734225
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ADHD in Predicting the Development of Violent Behavior Among Juvenile Offenders: Participation Versus Frequency

Abstract: Past research has identified attention-deficit/hyperactivity disorder (ADHD) as a risk factor for engagement in violent offending. Despite the link between the disorder and violent offending, this risk factor has yet to be examined as a predictor of heterogeneity in the development of violent offending among juvenile offenders. It is likely that the impulsivity, genetic link, and generally chronic disorder course which are characteristics of the disorder play roles in predicting violent offending, which is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…ADHD, a neurodevelopmental condition affecting approximately 7% of youth and 3% of adults (Rietz et al, 2020), is a strong risk factor for depression, antisocial behavior, and substance abuse disorders (Ohnishi et al, 2019). These enhanced risks may underlie some of the extremely poor psychosocial outcomes that are more common among those with ADHD: for example, school drop-out, unemployment, traumatic injuries, high healthcare utilization, financial debt, homelessness, intimate partner violence, violent crime, imprisonment, suicidality, and shorter life expectancy (Barkley & Fischer, 2019; Fleming et al, 2017; Gbessemehlan et al, 2020; Mordre et al, 2012; Rietz et al, 2020; Romero-Martinez et al, 2019; Wojciechowski, 2017). Mechanisms underlying connections between ADHD and its psychiatric comorbidities, in spite of their huge personal and societal costs, are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…ADHD, a neurodevelopmental condition affecting approximately 7% of youth and 3% of adults (Rietz et al, 2020), is a strong risk factor for depression, antisocial behavior, and substance abuse disorders (Ohnishi et al, 2019). These enhanced risks may underlie some of the extremely poor psychosocial outcomes that are more common among those with ADHD: for example, school drop-out, unemployment, traumatic injuries, high healthcare utilization, financial debt, homelessness, intimate partner violence, violent crime, imprisonment, suicidality, and shorter life expectancy (Barkley & Fischer, 2019; Fleming et al, 2017; Gbessemehlan et al, 2020; Mordre et al, 2012; Rietz et al, 2020; Romero-Martinez et al, 2019; Wojciechowski, 2017). Mechanisms underlying connections between ADHD and its psychiatric comorbidities, in spite of their huge personal and societal costs, are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by other research, although the influence of comorbid mental disorders, such as anti-social personality disorder (ASPD), is not yet fully understood [13,14]. For individuals with ADHD with a previous conviction, an elevated risk of recidivism has been observed [13,15,16].…”
Section: Introductionmentioning
confidence: 66%
“…This might indicate a link between offending alone and the presence of a persistent form of CD such as early-onset with an associated co-morbidity of ADHD. Research has shown that impulsivity is a risk factor for offending, with ADHD prevalence rates higher among violent than non-violent offenders (Young and Cocallis, 2019; Wojciechowski, 2017). However, studies with available longitudinal data have illustrated that when individuals have early features of ODD or CD, ADHD features are unable to consistently act as a signifier for persistent CD and serious offending in later life overall (Lahey et al , 2000; Frick and Moffit, 2010).…”
Section: Discussionmentioning
confidence: 99%